MORPHOLOGICAL AWARENESS IN TASK COMPLETION AND TEXT PROCESSING - Desi Marisi; Berlin Sibarani (REGISTER: Journal of English Language Teaching of FBS-Unimed, 2022)
The objectives of this study were to investigate the way of how morphological awareness tasks completion relates to morphological awareness in text processing and to find out the reason why the relation occurs the way it does. This study was conducted by using descriptive qualitative design. The participants were the students grade 8 of SMP Budi Murni Medan which consists of 25 students. This study revealed that there is different consistency between Text Processing Awareness and Completion Task for derivational morpheme and inflectional morphology. It was concluded that completion task is suitable for inflectional morpheme while for derivational morpheme it does not totally measure awareness, most of them measure ability to produce word. Furthermore, judgment task is the simplest of three tasks that measure the students’ awareness about morphological complex words. Some of the students have less awareness due to lack of vocabulary knowledge and the high frequency of words given.Keywords: morphological awareness, task completion, text processing